Characterization of Ralstonia solanacearum Which Causes Bacterial Wilt of Potato - Perera, A.A.U.; Dasanayaka, P.N.; Weerasena, O.V.D.S.J. (University of Sri Jayewardenepura, Nugegoda, 2015)
Bacterial wilt of potato caused by Ralstonia solanacearum is an important disease, causing huge losses worldwide, The estimated crop loss of potato due to bacterial wilt in Sri Lanka is around 5- 25% causing high financial losses to the growers. R. solanacearum is a Gram-negative, rod-shaped bacterium. Four biovars of the bacterium were distinguished and among them biovar I has not been recorded in Sri Lanka. This study was conducted to characterize the pathogen based on Badulla district which is one of the major potato producing areas in Sri Lanka, contributing about 75% of the production. Samples of wilted potato plants were collected from the fields in the areas of Kahagolla, Haputhalegama and Diyathalawa in the district. R. solanacearum was isolated on triphenyl tetrazolium chloride (TTC) agar medium using infected stem sections and tubers of the potato plant samples. Isolates were characterized biochemically using potassium hydroxide test, catalase test, oxidase test, citrate utilization test, nitrate test, starch hydrolysis test and gelatin liquefaction test. Genomic DNA of bacterial isolates was extracted using cetyltrimethyl ammonium bromide (CTAB) method and isolates were identified on molecular basis using species-specific primers, Rsol_fliC. Biovar of the isolates was determined based on their ability to utilize disaccharides and to oxidize hexose alcohols. Isolates of R. solanacearum from wilted potato plants produced mucoid, irregular, white colonies with red centres on TIC medium. According to biochemical tests isolates of R. solanacearum were Gram negative, positive for potassium hydroxide reaction, catalase activity, oxidase reaction, and citrate utilization, were able to reduce nitrate to nitrite and were negative for starch hydrolysis and gelatin liquefaction. In the polymerase chain reaction (PCR) with the RsolyiC primers, 06 isolates produced a 400 bp size amplicon, confirming their identity as R. solanacearum. All 06 isolates belonged to biovar 2, being able to utilize cellobiose, lactose and maltose, but not able to oxidize dulcitol, mannitol or sorbitol. The causal organism of bacterial wilt of potato in the selected areas was successfully characterized as R. solanacearum biovar 2.
Keywords: Potato; bacterial wilt; Ralstonia solanacearum; characterization; biovar